(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
The modernization of higher education systems and the growing demand for internationally competent specialists have significantly increased the importance of foreign language education. In non-philological higher education institutions, English is increasingly viewed not as an academic discipline in isolation, but as an essential instrument for professional development. This article examines the pedagogical foundations, principles, and practical implementation of teaching professionally oriented English through interdisciplinary integration. The study argues that the integration of English language instruction with major academic disciplines enhances students’ professional communicative competence, motivation, and cognitive engagement. The article analyzes current challenges, proposes methodological solutions, and substantiates the effectiveness of interdisciplinary approaches in English language teaching within non-philological universities.